Analysis and prioritization of sustainable livelihood alternatives for the Central Belize River Valley Communities - Charry, Andres; Claros Trujillo, Luisa María; Wiegel, Jennifer Rebecca (2023)
This report is a part of the EU DeSIRA project titled “Five Great Forests of Mesoamerica: A regional initiative for climate, biodiversity, and people” led by the Wildlife Conservation Society (WCS). It presents the findings of an assessment and prioritization exercise aimed at promoting sustainable livelihood alternatives among the communities of Central Belize River Valley. These communities interact, benefit, and protect the Maya Forest Corridor, a highly strategic landscape that connects the forests of northern Belize and the Guatemalan Maya Biosphere Reserve to the southern Maya Mountain Massif. The report aims to analyze and rate six alternatives against seven assessment criteria to determine their feasibility, potential, performance, and opportunities and limitations. The alternatives analyzed include backyard gardens, backyard animal production, non-timber forest products (focused on cohune nuts, cashew nuts, and wild berries), honey and hive products, tilapia, and cacao. The criteria employed for the analysis are market potential, community preferences, income generation potential, environment, social equity, enabling environment, and nutrition improvement potential. The results identify backyard gardens and backyard animal production as the alternatives with the highest success potential due to their alignment with the community’s preferences, capacities, and characteristics. However, there are limitations such as implementation costs for upscaling these systems and lack of expressed market interest at a commercial scale. Demand from public institutions and the hospitality sector has the capacity to absorb production surpluses. The potential of honey, tilapia, cacao, and NTFPs (Non-Timber Forest Products) such as cohune oil processing, has been evaluated. Honey reveals a relatively higher market and income generation potential, but the community preference for this product is generally low, except for a few individuals. The feasibility of cohune oil processing, tilapia, and cacao is limited and pose substantially larger capital demands. The results suggest pursuing a mix of productive projects tailored to the expressed interest and capacities of each beneficiary, with backyard gardens and animal production as the core activities. The productive alternatives should contemplate an integrated agroecological approach to reduce dependency on a single product.